4((-24+-1x)(3+-1x))=0

Simple and best practice solution for 4((-24+-1x)(3+-1x))=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4((-24+-1x)(3+-1x))=0 equation:


Simplifying
4((-24 + -1x)(3 + -1x)) = 0

Multiply (-24 + -1x) * (3 + -1x)
4((-24(3 + -1x) + -1x * (3 + -1x))) = 0
4(((3 * -24 + -1x * -24) + -1x * (3 + -1x))) = 0
4(((-72 + 24x) + -1x * (3 + -1x))) = 0
4((-72 + 24x + (3 * -1x + -1x * -1x))) = 0
4((-72 + 24x + (-3x + 1x2))) = 0

Combine like terms: 24x + -3x = 21x
4((-72 + 21x + 1x2)) = 0
(-72 * 4 + 21x * 4 + 1x2 * 4) = 0
(-288 + 84x + 4x2) = 0

Solving
-288 + 84x + 4x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '4'.
4(-72 + 21x + x2) = 0

Factor a trinomial.
4((-24 + -1x)(3 + -1x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-24 + -1x)' equal to zero and attempt to solve: Simplifying -24 + -1x = 0 Solving -24 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -1x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 0 + 24 -1x = 0 + 24 Combine like terms: 0 + 24 = 24 -1x = 24 Divide each side by '-1'. x = -24 Simplifying x = -24

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {-24, 3}

See similar equations:

| 18x^3+15x^2-9x= | | 3/4x3 | | 4cos^4x-1=0 | | km^2-c=n | | x^2-14+24=0 | | -13x-20=-11x-120 | | 7-2x/59 | | 110x(14-y)+950y=5740 | | 3.4*t+0.08=11 | | 110(14-y)+950y=5740 | | 3*a+2-5*a=-14 | | -2(2x-6)+9x=6+4(5x-1) | | (4x-9)/(3-4x) | | g=9/5(p-90) | | Log(x)=-3 | | -5x^2+5+10x=0 | | 4x^2+x+17=0 | | 7+(x-3)=6+x | | g(-1)=1-10(-1)-3 | | -64-4a-4=-28 | | 5(3x-2)+5=4-7(2x-1) | | 3x-105=180 | | 8-(3y-3)=6-4y | | ×=70/18 | | 5/4m-8/4 | | 3x^2-60x+120=0 | | -(7w-2z+5y)= | | 7x+8=6-(7x-4) | | 2-10x-5(2+x)=-26 | | 3*1+5=8 | | 42/13*29/14 | | 3x-20-5(x-8)=-2 |

Equations solver categories